Q. 16

# Prove the following by the principle of mathematical induction:2 + 5 + 8 + 11 + … + (3n – 1) = 1/2 n(3n + 1)

Answer :

Let P(n): 2 + 5 + 8 + 11 + … + (3n – 1) = n(3n + 1)

For n=1

P(1): 2 = .1.(4)

2 = 2

Since, P(n) is true for n = 1

Let P(n) is true for n = k, so

P(k): 2 + 5 + 8 + 11 + … + (3k – 1) = k(3k + 1) - - - - - - - (1)

We have to show that,

2 + 5 + 8 + 11 + … + (3k – 1) + (3k + 2) = (k + 1)(3k + 4)

Now,

{2 + 5 + 8 + 11 + … + (3k – 1)} + (3k + 2)

= .k(3k + 1) + (3k + 2)

=

=

=

=

=

=

Therefore, P(n) is true for n = k + 1

Hence, P(n) is true for all n N by PMI

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Prepare the Topic : Principle of Superpostion for Exams45 mins
Fundamental Principle of Counting49 mins
Game of Position & Momentum (Heisenberg Uncertainity principle)29 mins
Take the challenge, Quiz on Vectors37 mins
Vectors- Cosine & SIne Rule54 mins
Le Chatelier's Principle34 mins
Scalar and vector product in one shot56 mins
Revise Complete Vectors & it's application in 50 Minutes51 mins
Interactive Quiz on vector addition and multiplications38 mins
Scalar and Vector Product49 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses